2006
DOI: 10.1109/tpami.2006.208
|View full text |Cite
|
Sign up to set email alerts
|

Integral Invariants for Shape Matching

Abstract: Abstract-For shapes represented as closed planar contours, we introduce a class of functionals which are invariant with respect to the Euclidean group and which are obtained by performing integral operations. While such integral invariants enjoy some of the desirable properties of their differential counterparts, such as locality of computation (which allows matching under occlusions) and uniqueness of representation (asymptotically), they do not exhibit the noise sensitivity associated with differential quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(84 citation statements)
references
References 88 publications
0
82
0
2
Order By: Relevance
“…As mentioned earlier our method is based on the II scale space, which is inspired from Ref. [24] and eventually provides the basis for the RMA that we develop.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier our method is based on the II scale space, which is inspired from Ref. [24] and eventually provides the basis for the RMA that we develop.…”
Section: Methodsmentioning
confidence: 99%
“…II, which are fundamentally related to differential invariants, can be used effectively for shape representation [21] and reconstruction, [22] and are robust to noise. [21,23,24] Al-Kadi et al also measured feature robustness under noise presence in medical images and is reported in Refs. [25][26][27] II outperform differential invariants [28,29] for invariance to small perturbations in shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Hong defines (circular area) integral invariants in [5] by considering a disc $ å :L; of radius N applied to every point L Ð 5 of a closed contour ò5á that is the boundary of the shape 5. The characteristic function is then given by,…”
Section: Integral Invariantsmentioning
confidence: 99%
“…It is usually performed by producing a shape signature, which ideally is invariant to rigid or isometric transformations, such as, articulations, bending, translation, and rotation. Here, we combine two such techniques, the continuous eccentricity transform [1][2][3][4]12] and integral invariant signatures [5][6]. A detailed review of shape representation [7], matching and description techniques and categorical classification is given in [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation